How Facial Attractiveness Affects Time Perception: Increased Arousal Results in Temporal Dilation of Attractive Faces - Zhou, Sihong; Li, Lingjing; Wang, Fuyun; Tian, Yu (Frontiers in Psychology, 2021)
Time perception plays a fundamental role in people’s daily activities, and it is modulated by changes in environmental contexts. Recent studies observed that attractive faces generally resulted in temporal dilation and proposed increased arousal to account for such dilation. However, there is no direct empirical result to evidence such an account. The aim of the current study, therefore, was to clarify the relationship between arousal and the temporal dilating effect of facial attractiveness by introducing a rating of arousal to test the effect of arousal on temporal dilation (Experiment 1) and by regulating arousal via automatic expression suppression to explore the association between arousal and the temporal dilation (Experiment 2). As a result, Experiment 1 found that the increased arousal mediated the temporal dilating effect for attractive faces; Experiment 2 showed that the down-regulation of arousal attenuated the temporal dilation for attractive faces. These results highlighted the role of increased arousal, which is a dominating mechanism of the temporal dilating effect of attractive faces.